ANALISA KRITIS GUGATAN VOLUNTAIR TERHADAP PRAKTIK MALADMINISTRASI DI BIDANG PELAYANAN PUBLIK - Ade Kosasih (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2016)
The presence of concept positive fictitious decision in the Laws Of Administration of Government is an attempt to fight maladministration in the field of public service. In order to decision of positive fictitious get the laws power, Based on Laws Adpem should be applied for the determination to PTUN through lawsuit voluntair. Lawsuit voluntair is lawsuit petition affirmation of a right in the absence of other parties that made opponents (ex parte). If Lawsuit voluntair was granted by PTUN without the presence of the defendant, it could have voluntair lawsuit that originally expected to provide protection to the public, even cause new problems, For example court decision was contrary to the laws and regulations or prejudice the others. To avoid erroneous determination, then the judge in the lawsuit voluntair examination should be careful and cautious. The judge should instruct the defendant to attend and asked for information, although only as a witness and not as opponent. Furthermore, voluntair lawsuit could not be filed due to the passive attitude of the agency or government officials on a request for cancellation of the concrete decisions.